The Highland fling and how to teach it - Grant, Horatio N. (Buffalo, N.Y., Electric City Press, 1892)
This short pamphlet is devoted to the Highland Fling, described as a popular fancy dance, especially appropriate for children. The author gives four exercises and descriptions for eleven steps, many with multiple parts.
At head of title: "Book no. 2."
Available also through the Library of Congress Web site as facsimile page images and full text.
Keywords: Highland fling (Dance) -- Handbooks, manuals, etc; Dance Instruction and Technical Manuals; Theatrical Dance